Knowledge, attitudes, and practices toward exercises among women visiting an infertility clinic: A cross-sectional study. Issue 4 (3rd April 2023) - Gundimi, Shashwathi; Krishna Rao, Bhamini; Bailey, Ajay; Kumar, Pratap; Nair, Vipin; Velingkar, Kiransha R.; Ramachandra, Preetha
Abstract: Globally, there is a rising prevalence of infertility, and it has a negative consequence on the quality of life of women. The researchers aimed to understand the knowledge, attitude, and practice of women with infertility toward exercises. A cross-sectional study was conducted on 332 women aged between 18 and 45 years attending an infertility clinic in a tertiary hospital in Southern India. Participants filled a self-developed, content validated, pilot-tested questionnaire. Informants perceived stress and weight gain to be the major causes of infertility. Exercise was believed to improve fertilization by 55.4% of the participants, and walking and yoga were the preferred mode of exercises.